Comparative law as transnational law a decade of the German law journal - Miller, Russell A., 1969-; Zumbansen, Peer, 1966- (New York : Oxford University Press, 2012)
This book assembles the works of scholars from around the world, forming a contextual demonstration of the increasing encounters and tensions among legal cultures. In offering different approaches to an understanding of transnational law, the chapters also bring out the important consequences of a more global outlook in legal scholarship, legal practice, and legal education.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Comparative law; Law -- Germany; Law -- Europe